Kompetensi Pedagogik Guru Pendidikan Agama Kristen Dengan Menerapkan Faktor Kognitif Dalam Proses Pembelajaran Peserta Didik - Budiman Halawa (KHARISMATA: Jurnal Teologi Pantekosta, 2023)
The organization of Christian Religious Education (CRE) at present is not easy due to significant challenges related to developments that can influence the faith and spirituality of students. Learning difficulties refer to situations faced by students during their participation in the learning process, caused by disruptions in neurological (cognitive) and psychological functions, as well as other aspects. These learning difficulties can be experienced by students in both general academic aspects and more specific fields. The purpose of this research is to integrate cognitive principles into pedagogical competencies with the aim of enhancing the quality of teaching and learning. To achieve this objective, the research utilizes a qualitative approach, relying on data collection and analysis rather than statistical calculations. Additionally, the author conducted a literature review using relevant sources on the pedagogical competencies of CRE teachers, integrating cognitive factors into the learning process, providing analysis, and explanations. The results of this research are intended to help improve the professionalism of CRE teachers in delivering more engaging, relevant, and meaningful learning materials to students. It also aims to enhance the quality of Christian religious education, assisting students in understanding and internalizing Christian values within the context of their lives. Penyelenggaraan Pendidikan Agama Kristen saat ini tidaklah mudah karena dihadapkan pada tantangan berat yang terkait dengan perkembangan yang dapat mempengaruhi kehidupan iman dan spiritualitas peserta didik. Kesulitan belajar merujuk pada situasi yang dihadapi oleh peserta didik saat berpartisipasi dalam proses belajar karena gangguan dalam fungsi neurologis (kognitif) dan psikologis, serta gangguan pada aspek lainnya. Kesulitan belajar ini bisa dialami oleh peserta didik baik dalam aspek akademis secara umum maupun dalam bidang yang lebih spesifik. Tujuan dari penelitian ini adalah untuk mengintegrasikan prinsip kognitif ke dalam kompetensi pedagogik, dengan tujuan meningkatkan kualitas pembelajaran. Berdasarkan tujuan tersebut, penelitian ini memanfaatkan pendekatan kualitatif karena mengandalkan hasil dari pengumpulan dan analisis data, bukan dari perhitungan statistik. Selanjutnya, penulis melakukan kajian pustaka dengan memanfaatkan berbagai literatur yang relevan tentang kompetensi pedagogik guru PAK dengan mengintegrasikan faktor kognitif dalam proses pembelajaran dengan memberikan analisis dan penjelasan. Hasil dari penelitian ini yaitu untuk membantu meningkatkan profesionalisme guru PAK dalam menyampaikan materi pembelajaran yang lebih menarik, relevan, dan bermakna bagi peserta didik dan meningkatkan kualitas pembelajaran agama Kristen dan membantu peserta didik dalam memahami dan menginternalisasi nilai-nilai agama kristen dalam konteks kehidupan mereka.